2016
DOI: 10.1101/091991
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Melittin-induced alterations in morphology and deformability of human red blood cells using quantitative phase imaging techniques

Abstract: Melittin, the active molecule of apitoxin or bee venom, is a transmembrane protein, and it forms small pores on the cell membrane 1 . Once melittin binds to the lipid membranes of cells, toroid-shaped pores are formed and enable the leakage of molecules with the size of tens of kDa. It results in changes in the permeability of the cell membrane depending on the melittin concentration. As a pore-forming protein, melittin has been extensively studied from diverse aspects including its structure, binding mechanis… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3
1

Relationship

5
2

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 63 publications
0
11
0
Order By: Relevance
“…Furthermore, since the RI value of most biological specimen is linearly proportional to protein concentration [13,14], ODT provides quantitative information including protein concentration and dry mass. For these reasons, there are growing numbers of biological and medical studies employing ODT to investigate the physiology of various samples [4] including neuron cells [15,16], red blood cells [17][18][19][20], parasites in host cells [21,22], immune cells [23], bacteria [15,24], gold nanoparticles in live cells [25], embryos [26], live cells in a microfluidic channel [27][28][29], and blood cells in vivo [30].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, since the RI value of most biological specimen is linearly proportional to protein concentration [13,14], ODT provides quantitative information including protein concentration and dry mass. For these reasons, there are growing numbers of biological and medical studies employing ODT to investigate the physiology of various samples [4] including neuron cells [15,16], red blood cells [17][18][19][20], parasites in host cells [21,22], immune cells [23], bacteria [15,24], gold nanoparticles in live cells [25], embryos [26], live cells in a microfluidic channel [27][28][29], and blood cells in vivo [30].…”
Section: Introductionmentioning
confidence: 99%
“…Previously, ODT has been widely used to study various biological samples including red blood cells [15][16][17][18][19][20][21][22] however, we were unable to identify lymphocyte cell types due to their indistinguishable cellular morphology and biochemical characteristics.…”
Section: Identification Of Lymphocyte Cell Types Is Crucial For Undermentioning
confidence: 95%
“…Previously, ODT has been widely used to study various biological samples including red blood cells [15][16][17][18][19][20][21][22] , white blood cells (WBC) 23,24 , hepatocytes 25 , cancer cells 16,[26][27][28][29][30][31][32] , neurons 32,33 , bacteria 34,35 , phytoplankton 36 , and hair 37 . In our previous study, we reported that ODT enables the quantitative analysis of WBCs including lymphocytes and macrophages 23 .…”
mentioning
confidence: 99%
“…Furthermore, since the RI value of most biological specimen is linearly proportional to protein concentration [11,12], ODT provides quantitative information including protein concentration and dry mass. For these reasons, there are growing numbers of biological and medical studies employing ODT to investigate the physiology of various samples [3] including neuron cells [13,14], red blood cells [15][16][17], parasites in host cells [18,19], immune cells [20], bacteria [13,21], gold nanoparticles in live cells [22], embryos [23], live cells in a microfluidic channel [24][25][26], and blood cells in vivo [27].…”
Section: Introductionmentioning
confidence: 99%